Высоконаполненные алмазосодержащие композиционные материалы с керамико-полимерными матрицами - Зайцев, В.А.; Кузей, А.М. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
The structure of diamond-containing composite materials with polymer matrixes has been
investigated using methods of scanning electron microscopy. It is shown that performance characteristics of composite materials are determined by matrix structure. It is established that processing
of natural diamond using diamond-containing composite material results in formation of its defect
surface layer.